2004
DOI: 10.1080/01612840490506392
|View full text |Cite
|
Sign up to set email alerts
|

Belonging and Adapting: Mental Health of Bosnian Refugees Living in the United States

Abstract: The purpose of this study was to elucidate the experience of Bosnian refugees currently living in the United States. Using a phenomenological method, seven adult female Bosnian refugees each participated in an audio-recorded interview lasting from one to two hours. Two major themes emerged from the analyses of the text: belonging and adapting. Belonging included concepts of cultural memory, identity and difference, empathy and reciprocity, and perfection of speech. Adapting focused on coping with transitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 24 publications
3
39
0
3
Order By: Relevance
“…Factors that may influence immigrant's psychological well-being in resettlement countries might accord our findings be traced back to the pre-migration and migration processes. Many of the participants in this study expressed their anxiety regarding violence and discrimination in the pre-migration and migration periods, in line with a previous study in Sweden [23]. A study in Denmark has indicated a significant relationship between violence in pre-migration and decreasing psychological well-being in post-migration [24].…”
Section: Discussionsupporting
confidence: 70%
“…Factors that may influence immigrant's psychological well-being in resettlement countries might accord our findings be traced back to the pre-migration and migration processes. Many of the participants in this study expressed their anxiety regarding violence and discrimination in the pre-migration and migration periods, in line with a previous study in Sweden [23]. A study in Denmark has indicated a significant relationship between violence in pre-migration and decreasing psychological well-being in post-migration [24].…”
Section: Discussionsupporting
confidence: 70%
“…For instance, discordance when adapting to the main culture, and subsequent change of health behaviors, has been well documented during acculturation for a variety of groups. [19][20][21] Furthermore, groups as dissimilar as African Americans, American Indians, Alaskan natives and Russians express greater body satisfaction than whites. 8,22 Thus studies regarding how these groups determine their appropriate body weight might also discover more of a focus on being healthy versus appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The overall health of a refugee is influenced by factors such as migration, losses incurred in the home country, traumatic events encountered, and hardships survived during the transition including stays in refugee camps (Adams et al 2004;Keyes and Kane 2004). Mental and physical health problems may present as a result of past experiences and are prevalent among refugees.…”
Section: Health Of Tibetan Refugeesmentioning
confidence: 99%